The prevalence and association of stress with sleep quality among medical students - Abdullah I. Almojali; Sami A. Almalki; Ali S. Alothman; Emad M. Masuadi; Meshal K. Alaqeel (Springer, 2017)
Abstract Introduction Medical students tend to reduce their sleep, in an effort to adjust and cope with their workload and stressful environment. This study estimated the prevalence of and the relationship between poor sleep quality and stress among medical students. Methods This cross-sectional study was conducted using a stratified random sample of male and female medical students in King Saud bin Abdulaziz University for Health Sciences in Riyadh, Saudi Arabia. A self-administered questionnaire was distributed to assess sleep quality using the Pittsburgh Sleep Quality Index, and the stress level by using the Kessler Psychological Distress Scale. Results: A high prevalence of poor sleep quality (76%) and stress (53%) were found, with a statistically significant association (p < 0.001). Logistic regression indicated that students who are not suffering from stress are less likely to have poor sleep quality (OR = 0.28, p < 0.001), and the risk of having poor sleep quality is almost four times higher in students whose cumulative grade point average (GPA) is less than 4.25 (OR = 3.83, p = 0.01). Conclusion The study documents a statistically significant association between stress and poor sleep quality. A recommendation for the management of medical college is to establish academic counseling centers focusing in promoting good sleep hygiene and strengthening students' study skills and coping with their stressful environment.